KEPUASAN PERAWAT YANG BERHUBUNGAN DENGAN PERAN KASI KEPERAWATAN DALAM PENGAMBILAN KEPUTUSAN TERKAIT DENGAN KEBIJAKAN DI BIDANG KEPERAWATAN DI RSJD DR. RM. SOEDJARWADI KLATEN - Parjiyana, Parjiyana; Pratiwi, Arum (Jurnal Berita Ilmu Keperawatan, 2008)
Background : The result of attainment of performance is not quit of an applied by policy in a institution of is including also in this case hospital. Making of policy  is an process which is ussul in every system. System policy maker in area treatment of RSJD Dr. RM.  Soejarwadi Klaten structurally and formal is the Nursing Supervisor, arranging and controling activity of nurse in order to treatment duty execution. But that way policy which ought to be released by  Nursing Supervisor isn’t applicable fully yet. The mentioned cause disappearance between nurse expectation with applied policy, cause many factor influencing to  intake of policy.Target of this Research is : for knowing the relation between the satisfaction of nurse with role of Nursing Supervisor in decision making in RSJD Dr. RM. Soedjarwadi Klaten.Method Research : this research type is the non eksperimental with taken sampel cross sectional method in this research is all nurse which still active work and noted as officer in the RSJD Dr. RM Soedjarwadi Klaten ( total  population) : 86 responder. Data analysis for the verification of hypothesis use chi-square with alpha 0,05. Result of Research: showing p-value equal to 0,011. The value is compared to smaller of alpha 0,05, thereby can be pulled by conclusion that hypothesizing zero refused and research hypothesizing ( Ha) accepted.Conclusion : " there is a relation between the satisfaction of nurse with Role of Nursing Supervisor in decision making in RSJD Dr. R.M. Soedjarwadi Klaten".